A meta-analysis of the association between BRAF mutation and nonsmall cell lung cancer. Issue 14 (April 2017) - Cui, Guanghui; Liu, Donglei; Li, Weihao; Fu, Xiao; Liang, Youguang; Li, Yuhang; Shi, Wensong; Chen, Xiaofang; Zhao, Song
Abstract: Background: Previous studies investigating the association between BRAF mutations and nonsmall cell lung cancer (NSCLC) remain controversial. To address the issue, we performed an updated meta-analysis of related articles. Methods: We conducted a comprehensive literature search in the electronic databases including ISI Science Citation Index, EMBASE, PubMed, and CNKI (up to January 2016). The odds ratios (ORs) and 95% confidence interval (CI) were assessed based on random-effects or fixed-effects models according to the heterogeneity of eligible studies. Results: A total of 16 studies enrolled 11, 711 patients with NSCLC were involved in the meta-analysis. The overall BRAF mutation rate was 2.6% (303/11, 711). There was a significant association between BRAF mutations and adenocarcinomas (ADCs) in NSCLC compared with non-ADCs (OR = 3.96, 95% CI = 2.13–7.34, P < 0.0001). No significant difference was observed in smoking and stage in patients with BRAF mutations. However, a significant difference of BRAF mutation rate was observed between women and men (OR = 0.72, 95% CI = 0.55–0.95, P = 0.02). In addition, the BRAF V600E mutations were more frequent in women (OR = 0.45, 95% CI = 0.26–0.77, P = 0.004) and never smokers (OR = 0.12, 95% CI = 0.05–0.29, P < 0.00001). Conclusions: BRAF mutations in ADCS and female significantly increased the risk of NSCLC compared to non-ADCS and male, respectively. BRAFV 600E mutation in NSCLC patients was significantly associated with female and nonsmokers.